Meta-analyses of the association between the PPARGC1A Gly482Ser polymorphism and athletic performance - Ying, C.; Dongmei, W.; Pingping, Y.; Shenglan, Y.; Qing, C.; Zhi C. (Biology of Sport, 2019)
Peroxisome proliferator-activated receptor gamma coactivator 1alpha (PGC1alpha) encoded by the PPARGC1A gene is a vital regulator of glucose and fatty acid oxidation, mitochondrial biogenesis, and skeletal muscle fibre conversion. Several studies have investigated the association between PPARGC1A Gly482Ser polymorphism and athletic performance in humans. However, the results were contradictory. In the present study, two meta-analyses were performed to assess the association between the Gly482Ser polymorphism and endurance or power athletic performance to resolve this inconsistency. Ten articles were identified, including a total of 3,708 athletes and 6,228 controls. Higher frequencies of the Gly/Gly genotype (OR, 1.26; 95% CI, 1.11-1.42) and the Gly allele (OR, 1.29; 95% CI, 1.09-1.52) were observed in Caucasian endurance athletes. Furthermore, higher incidences of the Gly/Gly genotype (OR, 1.30; 95% CI, 1.16-1.46) and the Gly allele (OR, 1.22; 95% CI, 1.12-1.33) were observed in power athletes compared to controls. This finding demonstrates that the Gly/Gly genotype and the Gly allele of the PPARGC1A Gly482Ser polymorphism may facilitate athletic performance regardless of the type of sport, as well as providing solid evidence to support the possible influence of genetic factors on human athletic